Defending the Ignorance View of Sceptical Scenarios - Kraft, Tim (International journal for the study of skepticism, 2015)
What is the role of sceptical scenarios—dreams, evil demons, brains in a vat—in sceptical arguments? According to the error view, sceptical scenarios illustrate the possibility of massive falsity in one’s beliefs, whereas according to the ignorance view, they illustrate the possibility of massive ignorance not necessarily due to falsity. In this paper, the ignorance view is defended by surveying the arguments in favour of it and by replying to two pressing objections against it. According to the first objection, the ignorance view illicitly introduces the kk-principle into sceptical arguments. In reply I argue that kk is not less plausible than its main rival, the closure principle. According to the second objection, relying on veridical ignorance-possibilities contradicts the transparency of belief. In reply I introduce a version of transparency that is consistent with the ignorance view.